ANALISIS TINGKAT PEMAHAMAN MASYARAKAT DAN STRATEGI PENGELOLAAN REHABILITASI MANGROVE DI DESA PASIMARANNU KECAMATAN SINJAI TIMUR, KABUPATEN SINJAI - Musrafil Musrafil; Kasmawati Kasmawati; Hamsiah Hamsiah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2023)
The purpose of this study was to determine the level of community understanding and strategies for managing mangroves in Pasimarannu Village, East Sinjai District, Sinjai Regency. This research was conducted in Pasahkue Hamlet, Pasimarannu Village from March to April 2023. The method in this study was carried out by interviews and questionnaire assistance with 70 respondents as samples. As well as analyzed with Likert Scale Analysis to determine community understanding of mangrove rehabilitation and SWOT Analysis to determine strategic direction for mangrove management in Pasimarannu Village. The results showed that the level of community understanding of mangrove rehabilitation in Pasimarannu Village obtained an ecological understanding score of 65.83% (good category), participation understanding of 71.25% (good category), and understanding of rehabilitation with a value of 76.71% ( good category). There are 2 strategic priority directions for mangrove management in Pashakue Hamlet, Pasimarannu Village based on the position matrix, swot matrix and determining alternative strategic ranking priorities in the WO strategy, namely: 1. Providing support for mangrove management policies as coastal protection so that the number of mangroves can be maintained or added b. Increase planting mangroves and carrying out strict supervision.